Shell shock to PTSD : military psychiatry from 1900 to the Gulf War - Jones, Edgar, 1953- (Maudsley monographs, 2005)
Provides a thought-provoking evaluation of the history and practice of military psychiatry, and places its findings in the context of advancing medical knowledge and the developing technology of warfare.